Engineering a drug-inducible pyroptosis platform enables precise tumor suppression in colorectal cancer - Xiang Yao; Yu Wei; Yuan Gao; Lei Li; Junchi Liu; Wenmin Zhou; Tao Yan; Letian Gong; Yang Zhou; Ganglong Gao (Synthetic and Systems Biotechnology)
Colorectal cancer remains a leading cause of cancer-related mortality, with long-term survival rates hindered by chemoresistance and an immunosuppressive tumor microenvironment. Gene-based therapies offer high specificity but are limited by challenges such as off-target effects, inefficient delivery, and systemic toxicity. Here, we report the design and functional validation of a chemically inducible gene circuit that harnesses Gasdermin E (GSDME) to trigger pyroptotic cell death on demand. We substituted its native proteolytic activation motif with a customized protease recognition sequence. By engineering inducible protease variants whose activity is tightly regulated by an orally bioavailable, clinically approved small molecule, we achieved precise temporal control of pyroptosis. In patient-derived organoid models, administration of the inducer led to rapid GSDME cleavage, pore formation, and robust cell lysis. In a xenograft model, oral treatment with the approved drug led to marked tumor growth inhibition. This strategy utilizes the safety and pharmacokinetics of an approved drug to enable programmable cell death, providing a versatile platform for the targeted elimination of treatment-resistant tumors.